Actual problems of legal regulation of the Kyrgyz-Chinese relations in the field of intangible cultural heritage protection (Journal of actual problems of jurisprudence, 2019)
This article considers the legal and domestic aspects of regulation of dispute between the Kyrgyz Republicand the People’s Republic of China on the epic «Manas».Keywords: intangible cultural heritage, the UNESCO Convention, the epic «Manas» Kyrgyz-Chineserelations, a representative list of intangible cultural heritage of humanity, the protest public reaction inKyrgyzstan.